Hakikat Bermain Peran Di Sentra Main Peran Pada Anak Anak Usia Dini - Nur Anisyah (Insititut Agama Islam Negeri (IAIN) Curup, 2020)
Role-playing is a way of mastering learning materials through the development of imagination and student passion. The development and passion of the imagination is performed by students acting as a life or dead figure. This method involves a lot of students and makes them happy to learn. This learning method also has added value, which is to ensure the participation of all students and give the opportunity to cooperate successfully, so that it will cause an impression. Role-playing is a learning method as a simulated part that is geared towards creating historical events, creating actual events, or events that may arise in the future. Role-playing is one form of learning, where learners are actively involved in playing certain roles. Role-playing is something of a stage in which the player plays a specific role according to the already written play and played for entertainment purposes. Something related to education where the individual plays an imaginative situation in order to help achieve self-understanding, improve skills, demonstrate behavior to others how a person's behaviour or how one should behave. Role-playing is one of the learning tools that develops skills and understanding of the relationship between people by playing the path of parallel situations that occur in the actual life. The Learning Center's role-playing Model focuses on the child in the learning process centered around the play center and when the child is in a circle.